2017
DOI: 10.11591/ijeecs.v7.i2.pp442-448
|View full text |Cite
|
Sign up to set email alerts
|

Baggage Claim in Airports using Near Field Communication

Abstract: The popularity of public transportation has increased as infrastructures have been repaired and other supporting facilities have been added. One of the facilities which can be added in the transportation system is the implementation of Near Field Communication in order to accelerate each transaction in the transportation system. In airports, transaction activities need to be done efficiently, like claiming baggage at the baggage carousel. The speed of transaction to claim the baggage depends on the number of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Characteristics such as ease of use, secured communication channel, usage in different situation and the need to transfer data at high speed with very low energy together with some other advantages made the NFC technology to grow really fast and make big companies such as Sony, Samsung and Apple to embed this technology in their devices [3]. In a study conducted by Renardi et al on the characterizations and advantages of using NFC in public transportation, it has found that NFC could be used to support contactless transaction and data exchange with international standardization [4].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics such as ease of use, secured communication channel, usage in different situation and the need to transfer data at high speed with very low energy together with some other advantages made the NFC technology to grow really fast and make big companies such as Sony, Samsung and Apple to embed this technology in their devices [3]. In a study conducted by Renardi et al on the characterizations and advantages of using NFC in public transportation, it has found that NFC could be used to support contactless transaction and data exchange with international standardization [4].…”
Section: Introductionmentioning
confidence: 99%
“…While getting to their data mapping their precise data will be repetitive as the reported volume is gigantic. The electronic storage strategy replaces the customary technique for storing driver information where both physical and electronic strategies are utilized in parallel in this strategy [5]. The requirement for supplanting both these techniques turns out to be increasingly essential as these ideas become exhaustion.…”
Section: Background Studymentioning
confidence: 99%
“…In addition, NFC is also equipped with a device capable of setting the secure element [14]. These advantages make NFC suitable for applications that require secure storage and exchange of data via smart phones such as e-payment applications [15] & [16] or e-wallet [17], medical records [3], health services [18] & [19], and airport services [20]. The development of NFC-based medical record that will be conducted covers all media recording activities as well as qualified in the implementation of such activities.…”
Section: Near Field Communicationmentioning
confidence: 99%